The ecological and floristic characteristics of natural population of Micromeria juliana (L.) Benth. ex Rchb. in Bulgaria - Aneva, I.; Zhelev, P.; Nikolova, M.; Evtimov, I (Biologica Nyssana, 2016)
Micromeria juliana is a rare species in Bulgaria and is also a valuable medicinal plant. It is included in the Red Data Book of Bulgaria with conservation status “endangered” and is protected by the Biodiversity Act of Bulgaria. The present report focuses to the study of natural populations and plant communities of M. juliana in the two regions of its occurrence in Bulgaria – Eastern Rhodopes and the Valley of Mesta River. In the first locality the species grows on steep stony slopes and on walls of a medieval fortress, and the second one – on a steep calcareous slope, and on abandoned agricultural land. We present results of a survey on the species composition of plant communities of M. juliana together with analyses of floristic elements and ecological forms. The floristic composition indicates that the participation ratio of elements with Mediterranean origin is high. The ecological factors that have the highest impact on the floristic composition are intensive light, air temperature and humidity. The area occupied by the species is limited due to its very specific requirements and low competition ability.